Kolaborasi Mahasiswa dan Masyarakat Desa dalam Mengatasi Tantangan Sosial Melalui Program KKN di Desa Pisangan Jaya - Muhammad Fachri Azhar; Fitri Wahyu Rhamdani; Fitria Sisca Wulandari; Adrian Gilang Pamungkas; Juniar Amalia Saputri; Aura Risqita Andiany (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This community service program analyzes the impact of the Community Service Program (Kuliah Kerja Nyata - KKN) titled "Collaboration between Students and Rural Communities in Addressing Social Challenges through the KKN program in Pisangan Jaya Village." Pisangan Jaya Village, located in the Sepatan District, Tangerang Regency, Indonesia, faces various social challenges, including rapid population growth, changes in the job structure, and the preservation of agricultural land. This study aims to understand the contribution of the KKN program in addressing these challenges. Through impact evaluation, this community service program identifies improvements in the quality of life of the community, economic growth, and environmental improvements as outcomes of the program. The rural community actively participates in the planning and implementation of KKN projects, while students develop social skills and a deeper understanding of social challenges in rural areas. The evaluation results also reveal opportunities for improvement to strengthen project sustainability, more comprehensive planning, and student skill development. In conclusion, the KKN program in Pisangan Jaya Village has successfully facilitated close collaboration between students and rural communities to address social challenges and improve the quality of life.